ANTI-BACTERIAL EFFECTIVENESS OF Staphylococcus aureus FROM LIQUID SOAP PREPARATION FROM BELUNTAS LEAF ETHANOL EXTRACT (Pluchea indica L) - Candra Junaedi; Vicky Herdiny Hasyim; Nia Marlina (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
Beluntas leaves (Pluchea indica L.) is one of the plants that contain compounds such as flavonoids, alkaloids, tannins and saponins. This compound can be used to inhibit the growth of Staphylococcus aureus bacteria. The aim of this research is to make liquid bath soap preparation from ethanol extract beluntas leaves (Pluchea indica L.) and to know anthibactery activity against Staphylococcus aureus bacteria. The formula used in making liquid soap ethanol extract beluntas leaves (Pluchea indica L.) made with variation concentration 0%, 3%, 6% and 9%. The activity of extract of liquid soap beluntas leaves against the bacteria staphylococcus aureus by diffusion method using a concentration variation of 0%, 3%, 6% and 9% having the diameter of the inhibition zone respectively 4,48 mm, 6,23 mm and 7,3 mm. Statistical tests using parametic SPSS tests were carried out, the results obtained at concentrations of 6% and 9% had te same diameter inhibition zone, which was included in the category of moderate inhibition zone.